hub HUBUNGAN ANTARA BODY IMAGE DENGAN PENERIMAAN DIRI SISWA JURUSAN TEKNIK KOMPUTER DAN JARINGAN (TKJ) - Inten Anugraini; Yessy Elita; Anni Suprapti (UNIVERSITAS BENGKULU, 2024)
This research aims to describe the relationship between body image with self-acceptance among students majoring in Computer and Network Engineering (TKJ) at SMK Negeri 3 Bengkulu City. This research is correlation research. Data collection techniques use body image questionnaires and self-acceptance questionnaires. Data were analyzed using correlation pearson product moment. The research results show that there is a positive relationship between body image with self-acceptance among students with a value of 0.324. This means that there is a relationship between body image with self-acceptance among students majoring in Computer and Network Engineering (TKJ) at SMK Negeri 3 Bengkulu City. Keywords: adolescent, body image, self-acceptance